Factors perceived by employees that contribute to the promotion of health in the company and the impacts of the pandemic period (Research, Society and Development, 2022)
Health promotion is still not widespread in society however it involves political, social, environmental, behavioral and biological factors that can positively or negatively favor the health of the individual. In a business context, when properly applied, health promotion programs can generate effective results for the company, such as reducing absenteeism and improving productivity. Therefore, this study aims to identify how health promotion actions are perceived by employees of a specific company, Company X, also considering the possible impacts of the COVID-19 pandemic context. For that, it has as methodology the semi-structured interview with a pre-defined script with 13 employees from the administrative sector of the industrial park of a medium-sized company in the food industry in the city of Ji-Paraná, state of Rondônia; of qualitative character, the research adopts Laurence Bardin's Content Analysis method. In view of the results, it was found that, despite the initial difficulties for not knowing the concept of health promotion, the people interviewed were able to identify several actions carried out by Company X in this field; these actions were mostly related, directly or indirectly, to the corporate culture; and, although the pandemic period did not significantly change the way employees work in the company studied, it directly impacted some health promotion actions, especially those that involved fraternization and proximity in relationships.